Detection of erm genes in Staphylococcus lentus Erythromycin resistance isolated from Renal failure patients in Najaf province - Muna H. Al-Salamy; Mayyada F.Darweesh; Azhar N. Almousawi (Al-Qadisiyah Journal of Pure Science, 2018)
In this study was collected 600 samples from clinical and hospital environmental  sources from patients with renal failure (100 patients) auditors Sadr City Medical in Najaf and continuing on dialysis process for the period from June / 2014 and up to December / 2015 and divided the samples, according to sources gathered to 6 totals 100 samples for each of lactation, blood, arterial fistula, skin, bed and dialysis device. . Proven bacterial examination that the results of 208 (34.67)% samples did not show bacterial growth, while the samples showed bacterial growth and formed the 329 (65.34)%  samples diagnosed isolates based on phenotypic traits . Results showed 260 (66.33)% isolates gram positive and 132 (33.67)% isolated gram negative diagnosed depending on the biochemical tests and a vitek-2. Make examine the pharmacological sensitivity to 50 isolates towards 12 types of antibiotics, he found that most of the isolates of bacteria S.lentus has shown high resistance of up to 100% of the antibiotics Penicillin and Ceftazidime and 96% for Erythromycin and Clindamycin and 94% for Methicillin and 82% Cefotaxime and 78% for Ceftriaxone well Clavulanicacid / Amoxillin% 76 and 28% for Tetracycline well Sulfamethoxazole / Trimthoprim 20% and Levofloxacin 10%, but did not show any resistance Anti direction Vacomycin. The investigation of the genes of antibiotic resistance and examined 48 isolates resistance to the antibiotic erythromycin using the PCR technique of in order to detect genes responsible for the Erythromycin resistance and of gene ermA, ermB, ermC, rate was the presence of gene ermA% 27.8 13 isolated and 18 isolation owns gene ermB by 37.5% and gene ermC 62.5% from 30 isolated .